2021
DOI: 10.3389/fonc.2021.653141
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Stereotactic Body Radiotherapy in Patients With Hepatocellular Carcinoma Not Suitable for Transarterial Chemoembolization (HERACLES: HEpatocellular Carcinoma Stereotactic RAdiotherapy CLinical Efficacy Study)

Abstract: The aim of this prospective observational trial was to evaluate the efficacy, toxicity and quality of life after stereotactic body radiation therapy (SBRT) in patients with hepatocellular carcinoma (HCC) and to assess the results of this treatment in comparison to trans-arterial chemoembolization (TACE). Patients with HCC, treated with TACE or SBRT, over a period of 12 months, enrolled in the study. The primary endpoint was feasibility; secondary endpoints were toxicity, quality of life (QOL), local progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
0
5
0
3
Order By: Relevance
“…The 2021 HERACLES study was a prospective, 2-arm, nonrandomized study analyzing the role of SBRT and TACE in patients with HCC. 12 Patients received either TACE or SBRT according to the decision reached by the institution's tumor board. SBRT was indicated for patients who were not candidates for TACE or systemic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2021 HERACLES study was a prospective, 2-arm, nonrandomized study analyzing the role of SBRT and TACE in patients with HCC. 12 Patients received either TACE or SBRT according to the decision reached by the institution's tumor board. SBRT was indicated for patients who were not candidates for TACE or systemic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of patients treated with SBRT have shown similar cohort characteristics, specifically that SBRT cohorts have greater disease burden with high rates of previous treatment. The 2021 HERACLES study was a prospective, 2-arm, nonrandomized study analyzing the role of SBRT and TACE in patients with HCC 12 . Patients received either TACE or SBRT according to the decision reached by the institution’s tumor board.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of radiotherapy as stereotactic body radiotherapy (SBRT) has caused a resurge of the specialty in this scenario. Recent clinical data are progressively clarifying the differences between SBRT with other strategies, namely, trans-arterial chemoembolization (TACE), showing at least comparable outcomes in terms of toxicity and control outcomes ( 12 ). The rationale for selecting IORT and SRS as treatment schemes lies on the capacity of reproducing a surgical cavity from a tangible target structure.…”
Section: Discussionmentioning
confidence: 99%
“…In einer prospektiven nicht-randomisierten Beobachtungsstudie („HERACLES“), wurde die TACE mit der SBRT verglichen. Dabei lag die kumulative Inzidenz einer lokalen Progression nach 1, 2- und 3 Jahren bei 6 %, 6 % und 6 % nach der SBRT und bei 28 %, 39 % und 65 % nach TACE (p = 0.02) Die Lebensqualität war nach der SBRT nicht eingeschränkt und das Risiko für drittgradige Nebenwirkungen gering 332 . Bei der Durchführung der SBRT sollten Qualitätskriterien wie z.…”
Section: Diagnostik Und Therapie Des Hepatozellulären Karzinomsunclassified